Troubling meanings of family and competing moral imperatives in the family lives of young people with a parent who is at the end of life - Turner, Nicola; Almack, Kathryn (Taylor & Francis, 2017)
This article draws on a narrative study of young people with a parent who is at the end of life to examine how family lives are troubled by life-limiting parental illness. Young people struggled to reconcile the physical and emotional absence of family members with meanings of ‘family’; the extent to which young people could rely on family to ‘be there’ in these troubling circumstances was of practical, emotional and moral significance. Our discussion is situated in the context of an English end of life care policy predicated on the ideal of a good death as one that takes place at home accompanied by family members. We explore how the shift away from family as a site for nurturing children towards family as a space to care for the dying is experienced by young people, and consider how these competing moral imperatives are negotiated through relational practices of care.